Teori agensi : Teori agensi dalam perspektif akuntansi syariah - Said, Hilda Salman; Khotimah, Chusnul; Ardiansyah, Dekri; Khadrinur, Hanifah; Putri, Marsheli Indira (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The application of Islamic accounting in Islamic banking companies has developed. Sharia accounting has the principle of disclosure based on Allah's orders in accordance with the principles of Islamic law fully and openly in submitting its financial statements, therefore disclosure of halal and nonhalal transactions is required as a form of responsibility to the public in accordance with AAOIFI and PSAK standards. However, this application often causes problems in agency theory regarding conflicts of interest that are not commensurate between the principal and the management. Therefore, the purpose of this study is to find out the theory of agency in the perspective of Sharia accounting. The method used in this study is a literature study method, by looking for relevant reference theories based on existing cases or problems. The results of this study show that it is very necessary to present transparent financial statements in order to reduce agency problems so that this can show evidence so that there is no information hidden by each company. With the transparency of this report, it can show that managers have honest and trustworthy behavior and do not commit acts prohibited by religion.